2017
DOI: 10.3390/min7070126
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Effects on the Stability of Calcium Carbonate Pre-Nucleation Species

Abstract: Recent experimental evidence and computer modeling have shown that the crystallization of a range of minerals does not necessarily follow classical models and theories. In several systems, liquid precursors, stable pre-nucleation clusters and amorphous phases precede the nucleation and growth of stable mineral phases. However, little is known on the effect of background ionic species on the formation and stability of pre-nucleation species formed in aqueous solutions. Here, we present a systematic study on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 69 publications
(109 reference statements)
1
26
1
Order By: Relevance
“…Previously it was suggested that an increase in induction times, observed when CO 3 2À salts with smaller counter cations were used, was due to stabilisation of pre-nucleation clusters. 49 This conclusion contrasts with our observation, if we assume that D 2 O would also stabilise ion clusters. The longer induction times at [CO 3 2À ] = 48 mM in D 2 O may be indicative of the role of mass transport in .…”
Section: àcontrasting
confidence: 99%
“…Previously it was suggested that an increase in induction times, observed when CO 3 2À salts with smaller counter cations were used, was due to stabilisation of pre-nucleation clusters. 49 This conclusion contrasts with our observation, if we assume that D 2 O would also stabilise ion clusters. The longer induction times at [CO 3 2À ] = 48 mM in D 2 O may be indicative of the role of mass transport in .…”
Section: àcontrasting
confidence: 99%
“…Additives can influence ion association even without direct binding by modulating the water structure and introducing kosmotropic or chaotropic effects [36,37]. Due to the direct impact on the entropic balance of ion association through the release of hydration waters [38], these effects can increase or weaken ion-ion and/or ion-additive interactions [39], providing additional means to tune the strength of corresponding intermolecular interactions.…”
Section: Adsorption Of Free Ions and Pre-nucleation Clustersmentioning
confidence: 99%
“…External modulators of solvation also regulate the formation of PNCs from nanoscopic solute precursors. For instance, PNC‐associated ions and organic molecules presenting higher hydration contents hinder the dehydration of the ionic species, thereby enhancing the supersaturation levels required for particle nucleation ,. Thus, the nucleation process cannot be deconstructed to a simple aggregation‐based size evolution from individual ions to particles, but also is ingrained by the configurational and molecular nature of solute precursors in relation to their environment, (Figure a–c).…”
Section: On the Nature Of Materials Precursorsmentioning
confidence: 99%